Thermosetting conductive adhesive as well as preparation method and application thereof
By designing a thermosetting conductive adhesive containing functional epoxy resin, acrylate resin, curing agent and conductive filler, the problems of foreign matter formation and protection tape falling off in traditional lithium battery welding process are solved, and reliable bonding and high energy density between the electrode sheet and the ear of the lithium battery are achieved.
Patent Information
- Application Number
- CN202411958648.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-15
AI Technical Summary
During the production process of traditional lithium batteries, foreign matter such as burrs, welding slag, solder joints and metal particles caused by welding process increase the internal resistance of the battery cell and may cause short circuits and safety problems. At the same time, the protective tape is prone to fall off or deform during subsequent processing and use, affecting the protection effect.
A thermoset conductive adhesive is adopted, and its raw materials include functional epoxy resin, acrylate resin, curing agent and conductive filler. A stable crosslinking structure is formed through crosslinking reaction, which achieves the combination of high-temperature rapid curing and low-temperature slow curing, and has excellent adhesiveness, conductivity and electrolyte resistance.
This thermoset conductive adhesive realizes reliable connection in the bonding of the lithium battery electrode sheet and the ear, avoids burrs and metal particles during welding, and eliminates the need for protective tape, which improves the safety and energy density of the battery.
Smart Images

Figure BDA0005217715590000211 
Figure BDA0005217715590000231
Abstract
Description
Technical Field
[0001] The invention belongs to the field of chemical materials, and in particular relates to a thermosetting conductive adhesive and a preparation method and application thereof. Background Art
[0002] In the traditional lithium battery production process, the pole pieces and tabs of lithium batteries are generally connected using welding processes such as ultrasonic welding or laser welding. Foreign matter such as burrs, welding slag, welding points and metal particles generated during the welding process will lead to an increase in the internal resistance of the battery cell and the occurrence of internal short circuits in the battery cell.
[0003] In this regard, in the prior art, after the electrode and the lug are welded, a protective tape is usually applied to the surface of the welding position to prevent burrs, welding slag and welding points from piercing the diaphragm, and to prevent metal particles from falling into the battery cell and causing safety problems. However, the protective tape is attached to the surface of the welding position, which is easily corroded by the electrolyte during the subsequent lithium battery processing and use, and automatically falls off or deforms, losing its protective effect; and the attachment of the protective tape will cover the active material layer on the electrode, reducing the energy density of the battery.
[0004] In view of this, this application is hereby filed. Summary of the invention
[0005] The present application provides a thermosetting conductive adhesive and a preparation method and application thereof, aiming to solve or alleviate at least one technical problem existing in the above-mentioned prior art.
[0006] The first aspect of the present application provides a thermosetting conductive adhesive, the raw materials of which include a functional epoxy resin, an acrylate resin, a curing agent and a conductive filler; wherein the functional epoxy resin contains an epoxy group, and the functional epoxy resin and the acrylate resin are used to undergo a cross-linking reaction under the action of the curing agent.
[0007] The present application designs the raw material components of the thermosetting conductive adhesive, and adopts functional epoxy resin, acrylate resin, curing agent and conductive filler as the main raw materials; among them, acrylate resin and functional epoxy resin can give the thermosetting conductive adhesive bonding properties, acrylate resin has good adhesion, and when combined with functional epoxy resin, it can improve the bonding properties of the thermosetting conductive adhesive after curing and play a toughening role, while the functional epoxy resin can cooperate with the acrylate resin to promote the improvement of the heat and chemical resistance of the cured product of the thermosetting conductive adhesive, and improve the electrolyte resistance of the cured product; the curing agent can promote the cross-linking reaction of the acrylate resin and the functional epoxy resin during the curing process of the thermosetting conductive adhesive, so that the thermosetting conductive adhesive forms a stable cross-linked structure after curing; and the conductive filler can give the cured product of the thermosetting conductive adhesive conductive properties to meet the conductivity requirements when the lithium battery pole piece and the pole ear are connected.
[0008] During the curing process of the thermosetting conductive adhesive, the curing speed of the acrylate resin is faster than that of the functional epoxy resin. Under the action of the curing agent, the acrylate resin can undergo a curing reaction before the functional epoxy resin, so as to promote the rapid curing of the thermosetting conductive adhesive under high temperature (such as 180-250°C) conditions, and play a role in rapid positioning; the functional epoxy resin contains epoxy groups, and the epoxy groups can undergo a cross-linking reaction under the action of the curing agent; the functional epoxy resin is promoted to continue to cure during the curing process of the acrylate resin to form a cross-linking structure with the acrylate resin. Since the cross-linking structure formed by the curing of the thermosetting conductive adhesive is jointly formed during the curing process of the functional epoxy resin and the acrylate resin, the cross-linking structure has high stability. After curing, the thermosetting conductive adhesive can have high reliability, small dissolution and swelling rate, and excellent electrolyte resistance, so that the thermosetting conductive adhesive can have a high initial adhesion during the curing process, and strong electrolyte resistance after curing, and the cured product can maintain excellent adhesion and reliability.
[0009] Therefore, the thermosetting conductive adhesive provided by the present application realizes the combination of high-temperature rapid curing and low-temperature slow curing of the thermosetting conductive adhesive through the synergistic combination of raw material components such as functional epoxy resin, acrylate resin, curing agent and conductive filler. The cured thermosetting conductive adhesive not only has excellent solvent resistance and low dissolution and swelling rate, but also has excellent adhesion and reliability. The thermosetting conductive adhesive can be used in lithium batteries to achieve reliable bonding of the pole piece and the pole ear. The bonding layer formed by it is resistant to electrolyte corrosion and is not easy to detach from the pole piece or the pole ear. It can replace the welding connection used when connecting the traditional pole piece and the pole ear, thereby avoiding the formation of burrs, welding slag, welding spots and metal particles during welding, and there is no need to use protective tape to cover the pole piece, which effectively improves the safety and energy density of the battery.
[0010] In some embodiments, the raw materials of the thermosetting conductive adhesive include, by weight:
[0011] Functional epoxy resin: 1-10 parts; acrylate resin: 1-5 parts; curing agent: 0.1-5 parts; conductive filler: 20-45 parts.
[0012] In some embodiments, the functional epoxy resin further contains at least one active group, and the active group is used for coordinated cross-linking reaction with the acrylate resin under the action of a curing agent.
[0013] It should be noted that in addition to containing epoxy groups, the functional epoxy resin may also have at least one active group. Under the action of the curing agent, the epoxy group can continue to cure during the curing process of the acrylate resin, and the active group can synergistically cross-link with the acrylate resin under the action of the curing agent, and form chemical bonds during the synergistic cross-linking reaction, thereby effectively promoting the acrylate resin and the functional epoxy resin to form an integrated cross-linked structure after curing. Compared with the cross-linked structure in the form of an interpenetrating network structure, the integrated cross-linked structure has higher reliability, smaller dissolution and swelling rate, and better electrolyte resistance. After curing, the thermosetting conductive adhesive has better electrolyte resistance, and also has excellent adhesion and reliability.
[0014] In some embodiments, the active group includes at least one of a double bond or a hydroxyl group; optionally, the functional epoxy resin includes one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, aminophenol epoxy resin, and naphthol epoxy resin; optionally, the acrylate resin includes at least one of aliphatic polyurethane acrylate or polybutadiene-modified polyurethane acrylate; optionally, the curing agent includes a latent curing agent and a peroxide curing agent, and the mass ratio of the latent curing agent to the peroxide curing agent is (1-20):1.
[0015] In some embodiments, the raw materials of the thermosetting conductive adhesive also include at least one of a bismaleimide resin, a toughening agent or a diluent; optionally, in parts by weight, the raw materials of the thermosetting conductive adhesive include: 0.01-10 parts of bismaleimide resin; and / or, 0.01-5 parts of toughening agent; and / or, 0.01-5 parts of diluent.
[0016] In some embodiments, the thermosetting conductive adhesive satisfies at least one of the following conditions:
[0017] A, the peroxide curing agent comprises at least one of tert-butyl peroxy-2-ethylhexanoate, tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxybenzoate or dibenzoyl peroxide;
[0018] B. The latent curing agent includes at least one of an amine curing agent, a phosphorus curing agent or an imidazole curing agent;
[0019] C. The conductive filler includes at least one of superconducting carbon, graphite, hard carbon, silver powder, silver-coated copper powder, silver-coated nickel powder, nickel powder, silver-coated glass, silver-coated graphite, tin-silver-copper powder or carbon nanotubes; optionally, the particle size of the conductive filler is in the range of 0.2-100 μm;
[0020] D. bismaleimide resin includes at least one of N,N'-1,3-phenylene bismaleimide, 1,2-phenylene-bis-maleimide or N,N'-1,4-phenylene dimaleimide;
[0021] E. The toughening agent includes at least one of polybutadiene rubber or nitrile rubber;
[0022] F. The diluent includes at least one of a glycidyl ether diluent, a glycidyl ester diluent or a cyclobutane oxide diluent.
[0023] In some embodiments, the thermosetting conductive adhesive satisfies at least one of the following conditions:
[0024] G. Functional epoxy resins include at least one of Mitsubishi Chemical's jER 604, jER 630, Sumitomo Chemical's ELM-100H, DIC's 4032D, N730A, 7200H, ADEKA's 4088, or Shin-Nakamura Chemical's EA-1010N;
[0025] H. The acrylic resin includes at least one of Sandoma CN 966H90, CN 9014NS, BR-641S or BR-643;
[0026] I. The latent curing agent includes at least one of AJICURE PN-40, AJICURE PN-50, AJICURE MY-24, AJICURE MY-25 of Ajinomoto, FXR-1030, FXR-1081, FXE-1000 of Fuji, NOVACURE 3922HP, NOVACURE HX-A3932HP, NOVACURE HX-3941, NOVACURE HX-3042, NOVACURE HX-3742, NOVACURE HX-3088, HX-3792 of Asahi Kasei;
[0027] J. The toughening agent specifically includes at least one of epoxidized polybutadiene, polybutadiene-modified acrylate or core-shell rubber epoxy dispersion;
[0028] K. The diluent includes at least one of OXT-212, OXT-221, OXT-213, OXT-101 of East Asia Synthetics, ED509S of ADEKA, E10P of Momentive, EX201 of Nagase or GMA of Mitsubishi;
[0029] L. In parts by weight, the raw materials of the thermosetting conductive adhesive also include: epoxy-modified PP prepolymer: 1-10 parts; optionally, the molecular weight of the epoxy-modified PP prepolymer is 1000-100000.
[0030] The second aspect of the present application provides a method for preparing the above-mentioned thermosetting conductive adhesive, comprising uniformly mixing a functional epoxy resin, an acrylate resin, a curing agent and a conductive filler in a predetermined ratio to obtain a thermosetting conductive adhesive.
[0031] In some embodiments, the preparation method specifically comprises the following steps:
[0032] The first mixing stage: at least one of the optional bismaleimide resin, toughening agent or epoxy-modified PP prepolymer is mixed evenly with the functional epoxy resin and the acrylate resin to obtain a first mixed product;
[0033] The second mixing stage: adding the curing agent to the first mixed product and mixing evenly to obtain a second mixed product;
[0034] The third mixing stage: uniformly dispersing the conductive filler in the second mixed product to obtain a thermosetting conductive adhesive.
[0035] In some embodiments, the third mixing stage further comprises adding a predetermined proportion of a diluent to the thermosetting conductive adhesive and mixing; optionally, dispersing the conductive filler in the second mixed product comprises a first dispersion stage and a second dispersion stage performed in sequence; optionally, the first mixing stage, the second mixing stage and the third mixing stage are all performed under stirring conditions; optionally, in the first mixing stage or the second mixing stage: the stirring speed of the mixing container is controlled within the range of 5-60 rpm, and the stirring time is controlled within the range of 10-30 min; optionally, the stirring speed of the mixing container in the first dispersion stage is controlled within the range of 5-60 rpm, and the stirring time is controlled within the range of 10-30 min. The time is controlled within the range of 10-30min; optionally, the stirring speed of the mixing container in the second dispersion stage is controlled within the range of 30-100rpm, the dispersion speed of the mixing container is controlled within the range of 600-1000rpm, the stirring time is controlled within the range of 10-30min, and the mixing temperature is controlled below 30°C; optionally, adding a predetermined proportion of diluent to the thermosetting conductive adhesive includes a mixing stage and a vacuum degassing stage performed in sequence, and the stirring speed of the mixing container during the mixing stage and the vacuum degassing stage is controlled within the range of 5-60rpm, and the stirring time is controlled within the range of 10-30min.
[0036] The third aspect of the present application provides the above-mentioned thermosetting conductive adhesive, and its application in the bonding of lithium battery pole pieces and pole tabs. DETAILED DESCRIPTION
[0037] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0038] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0039] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0040] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0041] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may also include or contain other components not listed, or may only include or contain the listed components.
[0042] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0043] Based on the foregoing, the general inventive concept of the embodiment of the present application is to provide a thermosetting conductive adhesive. By designing the components of the thermosetting conductive adhesive, the thermosetting conductive adhesive has excellent bonding properties, conductivity and electrolyte resistance after thermal curing. When applied to the production process of lithium batteries, the pole pieces and the pole ears can be directly bonded with the thermosetting conductive adhesive to replace the traditional technology of connecting the pole pieces and the pole ears by welding, thereby avoiding the formation of burrs, welding slag, welding spots and metal particles during welding, and there is no need to use protective tape to cover the pole pieces, thereby effectively improving the safety and energy density of the battery.
[0044] Based on the above general inventive concept, an embodiment of the present application provides a thermosetting conductive adhesive, whose raw materials include functional epoxy resin, acrylate resin, curing agent and conductive filler; wherein, the functional epoxy resin contains epoxy groups, and the functional epoxy resin and acrylate resin are used to undergo a cross-linking reaction under the action of the curing agent.
[0045] It can be understood that the thermosetting conductive adhesive provided in this embodiment belongs to a mixed curing system. Among the components of the thermosetting conductive adhesive, the functional epoxy resin and the acrylate resin can give the thermosetting conductive adhesive bonding properties. The functional epoxy resin can cooperate with the acrylate resin to improve the bonding strength of the thermosetting conductive adhesive and promote the improvement of the heat resistance and chemical resistance of the cured product of the thermosetting conductive adhesive. The acrylate resin has good adhesion and can improve the bonding performance of the thermosetting conductive adhesive after curing when combined with the functional epoxy resin. At the same time, the acrylate resin can also play a toughening role, further improving the stability of the thermosetting conductive adhesive after curing. Both the acrylate resin and the functional epoxy resin can undergo a cross-linking reaction under the action of the curing agent to form a cross-linking structure together, so that the thermosetting conductive adhesive forms a stable cross-linking structure after curing; the conductive filler can give the thermosetting conductive adhesive a conductive property to the cured product, meeting the conductivity requirements when the lithium battery pole piece and the pole ear are connected.
[0046] Furthermore, during the curing process of the thermosetting conductive adhesive, the curing speed of the acrylate resin is faster than that of the functional epoxy resin. Under the action of the curing agent, the acrylate resin can undergo a curing reaction before the functional epoxy resin, thereby prompting the thermosetting conductive adhesive to cure quickly under high temperature (such as 180-250°C) conditions, playing a role in rapid positioning, so that the thermosetting conductive adhesive has a higher initial adhesion; since the functional epoxy resin contains epoxy groups, it can continue to cure under the action of the curing agent during the curing process of the acrylate resin, thereby forming a cross-linked structure with the acrylate resin, so that the thermosetting conductive adhesive can have a higher initial adhesion during the curing process, and the cured product formed after curing has strong electrolyte resistance, and can maintain excellent adhesion and reliability.
[0047] It should be noted that in addition to having excellent bonding properties, the thermosetting conductive adhesive should also have high electrolyte resistance because it will come into contact with the electrolyte when used for bonding lithium battery pole pieces and tabs, and various types of organic solvents are commonly present in the electrolyte. At the same time, heat will be generated during the charging and discharging process of the lithium battery, so the thermosetting conductive adhesive should also have high heat resistance. The cross-linked structure formed after the thermosetting conductive adhesive in the embodiment of the present application is conducive to fully leveraging the performance advantages of the main resins such as functional epoxy resins and acrylate resins. The cured product has high reliability, a small dissolution and swelling rate, and excellent electrolyte resistance.
[0048] At this point, the thermosetting conductive adhesive, through the synergistic effect of each component, can resist electrolyte corrosion after curing, and can still maintain a low dissolution swelling rate in an electrolyte containing a variety of solvents, and has excellent adhesion and conductivity. It can be used in lithium batteries to achieve reliable bonding between the pole piece and the pole ear, replacing the welding connection used in the traditional connection between the pole piece and the pole ear, and there is no need to use protective tape to cover the active material layer on the pole piece, which effectively improves the safety and energy density of the battery. In some embodiments, the raw materials of the thermosetting conductive adhesive include, by weight: functional epoxy resin: 1-10 parts; acrylate resin: 1-5 parts; curing agent: 0.1-5 parts; conductive filler: 20-45 parts.
[0049] For example, in the raw materials of the thermosetting conductive adhesive, the functional epoxy resin can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts or any parts by weight in the range of 1-10 parts; the acrylate resin can be 1 part, 1.5 parts, 2 parts, , 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts or any weight parts in the range of 1-5 parts; the curing agent can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, 1.1 part, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2 parts, 2. 1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5 or any weight part in the range of 0.1-5 parts; the conductive filler can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts or any weight part in the range of 20-45 parts.
[0050] The thermosetting conductive adhesive in this embodiment is designed with the above weight proportions of each raw material, so that each raw material component can give full play to its own performance advantages, so that the thermosetting conductive adhesive has excellent conductivity, adhesion and reliability after curing, low volume resistivity and strong solvent resistance, which is conducive to the reliable bonding of the electrode sheet and the electrode ear, thereby effectively improving the safety and energy density of the battery.
[0051] It should be understood that, if the functional epoxy resin is less than 1 part by weight, the strength of the thermosetting conductive adhesive after curing will be weak, the heat resistance and chemical corrosion resistance will be reduced, the swelling and dissolution rate in the electrolyte will be large, it will be easy to peel off from the substrate after soaking, and it will not be able to effectively form a stable cross-linking structure with the acrylate resin. If the functional epoxy resin is more than 10 parts by weight, the thermosetting conductive adhesive will have poor flexibility after curing, weak adhesion to the substrate, and will be easy to peel off from the substrate; if the acrylate resin is less than 1 part by weight, it will not be able to effectively form a stable cross-linking structure with the functional epoxy resin, which will make the thermosetting conductive adhesive take a long time to cure, and the adhesion to the substrate after curing will be weak, the toughness will be poor, and it will be easy to peel off from the substrate. If the acrylate resin is more than 5 parts by weight, the strength of the thermosetting conductive adhesive after curing will be poor, the electrolyte resistance will be poor, the peel strength of the cured product after soaking will be seriously reduced, and the adhesion and reliability will be poor.
[0052] Secondly, if the curing agent content is less than 0.1 parts by weight, the resin system is prone to incomplete curing and the reaction rate is too slow, resulting in unreacted groups or insufficient cross-linking in the cured product, thus affecting the bonding stability and reliability. If the curing agent content is higher than 5 parts by weight, the thermosetting conductive adhesive will cure too quickly, the internal stress will be large after curing, and the bonding performance and reliability of the cured product will be poor.
[0053] In addition, when the conductive filler is less than 20 parts by weight, the volume resistivity of the thermosetting conductive adhesive is relatively high after curing. When the thermosetting conductive adhesive is used for bonding the pole piece and the pole ear, the energy density of the battery is limited; when the conductive filler is greater than 45 parts by weight, it is easy to be unevenly distributed in the cured product to form agglomeration or precipitation, which affects the stability and reliability of the conductive product during conduction; therefore, the conductive filler is designed to be 20-45 parts, and based on the adhesive layer formed by the cured product, the pole piece and the pole ear can achieve vertical conduction based on the adhesive layer interface, so as to improve the stability and reliability of the pole piece and the pole ear during conduction, and ensure that the energy density of the battery is not limited.
[0054] In some embodiments, the functional epoxy resin further contains at least one active group, and the active group is used for coordinated cross-linking reaction with the acrylate resin under the action of a curing agent.
[0055] It can be understood that the functional epoxy resin in the embodiment of the present application may have at least one active group in addition to the epoxy group. When the functional epoxy resin contains the active group, the functional epoxy resin can continue to cure during the curing process of the acrylate resin. At the same time, the active group can synergistically cross-link with the acrylate resin under the action of the curing agent, and form chemical bonds during the synergistic cross-linking reaction, so that the acrylate resin and the functional epoxy resin can be combined to form an integrated cross-linked structure after curing. Compared with the interpenetrating network structure, the integrated cross-linked structure has higher reliability, smaller dissolution and swelling rate, and better electrolyte resistance. After curing, the thermosetting conductive adhesive has better electrolyte resistance, excellent adhesion and reliability.
[0056] It should be understood that the cross-linked structure in the form of an interpenetrating network structure in the embodiment of the present application refers to a network structure formed by cross-linking of molecular chains of multiple resins. Compared with the integrated cross-linked structure, the interpenetrating network structure swells slightly larger and has a slightly lower adhesion after soaking; and the integrated cross-linked structure refers to a three-dimensional network macromolecular cross-linked structure formed by connecting multiple resin molecular chains through side chains or chemical bonds. The reliability of the integrated cross-linked structure is greater than that of the interpenetrating network structure, and the electrolyte resistance is better.
[0057] In addition, the functional epoxy resin in the embodiment of the present application can be at least one functional epoxy resin having an epoxy group and not having the above-mentioned active group, or can be at least one functional epoxy resin having an epoxy group and having the above-mentioned active group, or a combination of the above-mentioned two functional epoxy resins; the introduction of the functional epoxy resin having the above-mentioned active group is more conducive to the thermosetting conductive adhesive having better electrolyte resistance after curing, while also having excellent adhesion and reliability.
[0058] In some embodiments, the active group includes at least one of a double bond or a hydroxyl group; the double bond or the hydroxyl group can cooperate with the acrylate resin to undergo a cross-linking reaction under the action of a curing agent to form an integrated cross-linking structure, thereby enabling the thermosetting conductive adhesive to have excellent conductivity, adhesion and reliability after curing, lower volume resistivity and stronger solvent resistance.
[0059] In some embodiments, the functional epoxy resin includes one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, aminophenol epoxy resin, and naphthol epoxy resin. As functional epoxy resins, the above substances all have epoxy groups and optional active groups, which are conducive to forming a stable cross-linking structure with the acrylate resin under the action of a curing agent, so that the thermosetting conductive adhesive has excellent electrolyte resistance after curing, and at the same time has good adhesion and reliability.
[0060] In some embodiments, the acrylate resin includes at least one of aliphatic polyurethane acrylate or polybutadiene-modified polyurethane acrylate; the above substances, when used as a combination of acrylate resin and functional epoxy resin, can improve the bonding performance of the thermosetting conductive adhesive after curing and shorten the curing time. At the same time, the acrylate resin can also play a toughening role, further improving the stability of the thermosetting conductive adhesive after curing.
[0061] In some embodiments, the curing agent includes a latent curing agent and a peroxide curing agent. The latent curing agent can promote the ring-opening reaction of the epoxy group of the functional epoxy resin, while the peroxide curing agent can promote the cross-linking reaction of the acrylate resin, and when the functional epoxy resin also contains active groups, the active groups are promoted to cross-link with the acrylate resin to form chemical bonds, so as to facilitate the formation of a stable cross-linking structure after the thermosetting conductive adhesive is cured.
[0062] In some embodiments, the mass ratio of the latent curing agent to the peroxide curing agent is (1-20): 1. Within this mass ratio range, the latent curing agent can better initiate the ring-opening reaction of the epoxy group of the functional epoxy resin, and the peroxide curing agent can better promote the cross-linking reaction of the acrylate resin, and promote the active groups to synergistically cross-link with the acrylate resin to form chemical bonds.
[0063] In some embodiments, the raw material of the thermosetting conductive adhesive further includes at least one of a bismaleimide resin, a toughening agent, or a diluent.
[0064] Bismaleimide resin is a bifunctional compound with maleimide (MI) as the active end group, with good aging performance, relatively strong solvent erosion resistance, good electrolyte resistance, glass transition temperature (Tg) generally greater than 250°C, and a service temperature range of generally about 177-232°C; since bismaleimide resin contains benzene rings and imide heterocycles on its molecular chain, bismaleimide resin has the same curing mechanism as acrylate resin and is cured under the action of peroxide curing agent, but its curing speed is slower than that of acrylate resin. During the curing process of acrylate resin, it can be continuously cured in coordination with functional epoxy resin, thereby further improving the crosslinking density of the thermosetting conductive adhesive after curing, and making its cured product have better heat resistance and electrolyte resistance.
[0065] The introduction of toughening agent can further improve the electrolyte resistance of thermosetting conductive adhesive after curing, and at the same time can play a toughening role to reduce the stress generated during the curing process and improve the thermal shock resistance of the cured product. Diluent is mainly used to adjust the viscosity of thermosetting conductive adhesive to an appropriate range to facilitate rapid construction and improve the production efficiency of lithium batteries.
[0066] In some embodiments, in the raw materials of the thermosetting conductive adhesive, by weight: 0.01-10 parts of bismaleimide resin; and / or 0.01-5 parts of toughening agent; and / or 0.01-5 parts of diluent.
[0067] For example, in parts by weight, the bismaleimide resin can be 0.01 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts or any parts by weight in the range of 0.01-10 parts. The bismaleimide resin in the range of 0.01-10 parts is more conducive to improving the crosslinking density of the thermosetting conductive adhesive after curing, so that the cured product has better heat resistance and electrolyte resistance. The toughening agent can be 0.01 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 5 parts or any parts by weight in the range of 0.01-5 parts, so as to further improve the electrolyte resistance of the thermosetting conductive adhesive after curing, and at the same time can play a toughening role to reduce the stress generated during the curing process and improve the thermal shock performance of the cured product; the diluent can be 0.01 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 5 parts or any parts by weight in the range of 0.01-5 parts, so as to adjust the viscosity of the thermosetting conductive adhesive to an appropriate range.
[0068] Peroxide curing agent is a class of compounds containing peroxy groups (-OO-). When heated, the -OO- bond breaks and splits into two corresponding free radicals, thereby initiating polymerization. In some embodiments, the peroxide curing agent includes at least one of tert-butyl peroxy-2-ethylhexanoate, tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxybenzoate or dibenzoyl peroxide; the above substances as peroxide curing agents all have peroxy groups and can initiate cross-linking reactions of active groups of functional epoxy resins, acrylate resins or bismaleimide resins.
[0069] In some embodiments, the latent curing agent includes at least one of an amine curing agent, a phosphorus curing agent or an imidazole curing agent; the above substances as latent curing agents can all trigger the epoxy groups of the functional epoxy resin to undergo a cross-linking reaction.
[0070] In some embodiments, the conductive filler includes at least one of superconducting carbon, graphite, hard carbon, silver powder, silver-coated copper powder, silver-coated nickel powder, nickel powder, silver-coated glass, silver-coated graphite, tin-silver-copper powder or carbon nanotubes; the above substances all have good conductive properties, and as conductive fillers, they can give the cured product of the thermosetting conductive adhesive excellent conductivity to meet the conductive requirements when connecting the lithium battery pole piece and the pole ear.
[0071] In some embodiments, the particle size of the conductive filler is in the range of 0.2-100 μm, so as to facilitate uniform dispersion of the conductive filler in the cured product of the thermosetting conductive adhesive.
[0072] In some embodiments, the bismaleimide resin includes at least one of N,N'-1,3-phenylene bismaleimide, 1,2-phenylene-bis-maleimide or N,N'-1,4-phenylene dimaleimide; the above substances are all bifunctional compounds with maleimide (MI) as the active end group. As a bismaleimide resin, it is beneficial to increase the cross-linking density of the thermosetting conductive adhesive after curing, so that its cured product has excellent heat resistance.
[0073] In some embodiments, the toughening agent includes at least one of polybutadiene rubber or nitrile rubber; polybutadiene rubber or nitrile rubber can effectively reduce the stress during the curing process of the thermosetting conductive adhesive and improve the hot and cold shock resistance of the thermosetting conductive adhesive after curing. Some specific configurations of polybutadiene rubber or nitrile rubber also have a good promoting effect on the electrolyte resistance of the cured product of the thermosetting conductive adhesive.
[0074] In some embodiments, the diluent includes at least one of a glycidyl ether diluent, a glycidyl ester diluent or an oxide cyclobutane diluent; the above substances as diluents can adjust the viscosity of the thermosetting conductive adhesive to a suitable state, so that when the thermosetting conductive adhesive is used for bonding the pole ears and pole pieces, continuous spraying construction can be adopted to improve production efficiency.
[0075] In some embodiments, the functional epoxy resin includes at least one of Mitsubishi Chemical's jER 604, jER 630, Sumitomo Chemical's ELM-100H, DIC's 4032D, N730A, 7200H, ADEKA's 4088, or Shin-Nakamura Chemical's EA-1010N; all of the above substances have epoxy groups to facilitate continuous curing during the curing process of the acrylate resin, and under the action of the curing agent, they undergo a cross-linking reaction with the acrylate resin to form a stable cross-linked structure.
[0076] It should be noted that Sumitomo Chemical's ELM-100H contains epoxy groups but does not contain the above-mentioned active groups, while Shin-Nakamura Chemical's EA-1010N contains both epoxy groups and the above-mentioned active groups.
[0077] In some embodiments, the acrylate resin includes at least one of Sadomar CN 966H90, CN 9014NS, BR-641S or BR-643; the above substances as acrylate resins all belong to the peroxide curing system, and quickly cure under the action of the curing agent, and form a cross-linked structure together with the curing of the functional epoxy resin. In addition, when the functional epoxy resin contains active groups, it can also synergistically cross-link with the functional epoxy resin during the curing process, so as to improve the electrolyte resistance of the thermosetting conductive adhesive after curing and play a toughening role.
[0078] In some embodiments, the latent curing agent includes at least one of AJICURE PN-40, AJICURE PN-50, AJICURE MY-24, AJICURE MY-25 of Ajinomoto, FXR-1030, FXR-1081, FXE-1000 of Fuji, NOVACURE3922HP, NOVACURE HX-A3932HP, NOVACURE HX-3941, NOVACURE HX-3042, NOVACURE HX-3742, NOVACURE HX-3088, HX-3792 of Asahi Kasei; the above substances as latent curing agents can initiate the ring-opening polymerization of the epoxy groups of the functional epoxy resin, thereby effectively promoting the formation of a cross-linked structure between the acrylate resin and the epoxy resin after curing.
[0079] In some embodiments, the toughening agent specifically includes at least one of epoxidized polybutadiene, polybutadiene-modified acrylate or core-shell rubber epoxy dispersion (the core part is polybutadiene or nitrile rubber, and the shell part is alicyclic epoxy resin); epoxidized polybutadiene, polybutadiene-modified acrylate or core-shell rubber epoxy dispersion as polybutadiene rubber or nitrile rubber are all liquid rubbers, specifically, such as the MX series of core-shell rubbers of Japan's KANEKA, including dispersions of core-shell rubbers of NBR (nitrile rubber) and CTBN (carboxyl-terminated liquid nitrile rubber), POLYBD resins of the RICON series of Crayville, etc.; polybutadiene rubber or nitrile rubber can also use solid rubbers such as core-shell rubber powder.
[0080] In some embodiments, the diluent includes at least one of a glycidyl ether diluent, a glycidyl ester diluent or an oxide cyclobutane diluent, for example, it may include at least one of OXT-212, OXT-221, OXT-213, OXT-101 of East Asia Synthetics, ED509S of ADEKA, E10P of Momentive, EX201 of Nagase or GMA of Mitsubishi; the above substances as diluents can reduce the viscosity of thermosetting conductive adhesives and have little effect on the performance of the formed cured product.
[0081] In some embodiments, the raw materials of the thermosetting conductive adhesive further include, by weight: epoxy-modified PP prepolymer: 1-10 parts. It should be noted that the epoxy-modified PP prepolymer can be obtained by grafting epoxy groups on the molecular chain of hydroxy-modified PP or maleic anhydride-grafted PP, and the grafted epoxy groups are aliphatic epoxy groups, so that the epoxy-modified PP prepolymer has a lower polarity, which is beneficial to improve the electrolyte resistance. Under the action of the curing agent, the epoxy-modified PP prepolymer participates in the curing reaction of the thermosetting conductive adhesive, which significantly improves the electrolyte resistance of the cured product of the thermosetting conductive adhesive. Therefore, by introducing 1-10 parts of epoxy-modified PP prepolymer into the thermosetting conductive adhesive component, the epoxy-modified PP prepolymer can replace part of the toughening agent, further enhancing the electrolyte resistance of the cured product.
[0082] In some embodiments, the molecular weight of the epoxy-modified PP prepolymer is 1000-100000 to ensure good dispersibility and reactivity in the system.
[0083] Another embodiment of the present application provides a method for preparing the thermosetting conductive adhesive as described in the above embodiment, comprising uniformly mixing raw materials such as functional epoxy resin, acrylate resin, curing agent and conductive filler in a predetermined ratio to obtain a thermosetting conductive adhesive.
[0084] Furthermore, the preparation method of the thermosetting conductive adhesive specifically includes the following steps:
[0085] The first mixing stage: at least one of the optional bismaleimide resin, toughening agent or epoxy-modified PP prepolymer is mixed evenly with the functional epoxy resin and the acrylate resin to obtain a first mixed product;
[0086] The second mixing stage: adding the curing agent to the first mixed product and mixing evenly to obtain a second mixed product;
[0087] The third mixing stage: uniformly dispersing the conductive filler in the second mixed product to obtain a thermosetting conductive adhesive.
[0088] In some embodiments, the third mixing stage further includes adding a predetermined proportion of diluent into the thermosetting conductive adhesive and mixing the mixture to reduce the viscosity of the thermosetting conductive adhesive and facilitate the construction when the thermosetting conductive adhesive is used for bonding.
[0089] Furthermore, dispersing the conductive filler in the second mixed product includes a first dispersing stage and a second dispersing stage performed sequentially, so as to facilitate uniform dispersion of the conductive filler.
[0090] Furthermore, the first mixing stage, the second mixing stage and the third mixing stage are all carried out under stirring conditions, so that the components can be fully mixed.
[0091] Furthermore, in the first mixing stage or the second mixing stage: the stirring speed of the mixing container is controlled within the range of 5-60 rpm, and the stirring time is controlled within the range of 10-30 min, so as to facilitate the mixing of the components in the first mixed product or the second mixed product.
[0092] Furthermore, in the first dispersing stage, the stirring speed of the mixing container is controlled within the range of 5-60 rpm, and the stirring time is controlled within the range of 10-30 min, so as to facilitate the conductive filler to be fully mixed into the second mixed product.
[0093] Furthermore, in the second dispersion stage, the stirring speed of the mixing container is controlled within the range of 30-100 rpm, the dispersion speed of the mixing container is controlled within the range of 600-1000 rpm, the stirring time is controlled within the range of 10-30 min, and the mixing temperature is controlled below 30° C., so as to facilitate uniform dispersion of the conductive filler.
[0094] It should be noted that the third mixing stage uses a double planetary stirring kettle as a mixing container to facilitate accurate control of the stirring speed of the first dispersing stage and the second dispersing stage.
[0095] Furthermore, adding a predetermined proportion of diluent to the thermosetting conductive adhesive includes a mixing stage and a vacuum degassing stage performed sequentially. During the mixing stage and the vacuum degassing stage, the stirring speed of the mixing container is controlled within the range of 5-60rpm, and the stirring time is controlled within the range of 10-30min, respectively, to reduce the viscosity of the thermosetting conductive adhesive and avoid bubbles remaining in the thermosetting conductive adhesive.
[0096] In some embodiments, when the thermosetting conductive adhesive introduces an epoxy-modified PP prepolymer component, as an example, the epoxy-modified PP prepolymer can be prepared by prepolymerizing epoxy reactive diluent and maleic anhydride grafted polypropylene (MAH-g-PP) as raw materials under the action of a catalyst, specifically comprising the following steps: weighing MAH-g-PP and adding it into a reaction container, heating it to 150°C for melting; weighing the epoxy reactive diluent and adding it into the reaction container, evacuating the container, and controlling the stirring speed at 200-500rpm to uniformly mix the reaction system; after uniform mixing, adding a catalyst into the reaction container, raising the temperature to 170°C, ensuring that the temperature in the reaction container is 160°C±5°C, reacting for 1-3h, and the entire reaction process is carried out in a vacuum environment; after the reaction is complete, the material is discharged and cooled to obtain an epoxy-modified PP prepolymer.
[0097] In the preparation process of the epoxy-modified PP prepolymer, the epoxy active diluent includes at least one of polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, and hexanediol diglycidyl ether; the molecular weight of maleic anhydride grafted polypropylene is 1000-50000, such as Dow's GA1000R, Mitsui's ADMER series, etc.; the catalyst can be at least one of triphenylphosphine, N,N-dimethylaniline, triethylamine, tetramethylammonium bromide or tetraethylammonium bromide. In the preparation process of the epoxy-modified PP prepolymer, the mass ratio of epoxy active diluent to maleic anhydride grafted polypropylene can be (8-10): 1, and the catalyst accounts for 1%-2% of the total mass percentage.
[0098] Another embodiment of the present application provides the above-mentioned thermosetting conductive adhesive, which is used in bonding lithium battery pole pieces and tabs.
[0099] When the thermosetting conductive adhesive in this embodiment is used for bonding lithium battery pole pieces and tabs, it has excellent adhesion to metal aluminum, metal nickel, and metal copper, and has high shear strength. It can complete preliminary curing or complete curing within 1 to 6 seconds at 180 to 250°C, and can be completely cured within 4 hours at 85 to 110°C. It has been verified by experiments that the cured product has a low dissolution rate and swelling rate in an electrolyte environment, and can achieve stable and reliable bonding of lithium battery pole pieces and tabs. The cured product can still maintain a high bonding stability under long-term electrolyte erosion, which effectively improves the safety and energy density of the battery compared to the method of connecting the tabs and pole pieces by welding.
[0100] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, the conditions are carried out according to normal conditions or manufacturer recommendations. The reagents used or the instruments that do not specify the manufacturer are all conventional products that can be purchased commercially. In the following examples and comparative examples, raw materials are all measured by weight.
[0101] Example 1
[0102] First mixing stage: 4 parts of functional epoxy resin 1, 4 parts of acrylate resin 1 and 1 part of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;
[0103] Second mixing stage: add 1.5 parts of curing agent 1 and 0.1 parts of curing agent 2 to the first mixed product and mix them, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;
[0104] The third mixing stage: add 40 parts of conductive filler 1 and 1 part of conductive filler 2 to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes to obtain a thermosetting conductive adhesive; then add 1 part of diluent to the thermosetting conductive adhesive, control the stirring speed to 30 rpm, stir for 10 minutes, and continue stirring for 20 minutes in a vacuum environment, then discharge the material to obtain a thermosetting conductive adhesive A1.
[0105] Example 2
[0106] First mixing stage: 3 parts of functional epoxy resin 1, 1 part of functional epoxy resin 2, 2 parts of acrylate resin 1 and 2 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;
[0107] Second mixing stage: add 1.5 parts of curing agent 1 and 0.1 parts of curing agent 2 to the first mixed product and mix them, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;
[0108] The third mixing stage: add 40 parts of conductive filler 1 and 1 part of conductive filler 2 to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes to obtain a thermosetting conductive adhesive; then add 2 parts of diluent to the thermosetting conductive adhesive, control the stirring speed to 30 rpm, stir for 10 minutes, and continue stirring for 20 minutes in a vacuum environment, then discharge the material to obtain a thermosetting conductive adhesive A2.
[0109] Example 3
[0110] First mixing stage: 3 parts of functional epoxy resin 1, 3 parts of functional epoxy resin 2, 2 parts of acrylate resin 1 and 2 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;
[0111] Second mixing stage: add 1.5 parts of curing agent 1 and 0.1 parts of curing agent 2 to the first mixed product and mix them, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;
[0112] The third mixing stage: add 38 parts of conductive filler 1 and 1 part of conductive filler 2 to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes, and obtain thermosetting conductive adhesive A3.
[0113] Example 4
[0114] First mixing stage: 1 part of functional epoxy resin 1, 1.5 parts of acrylate resin 1, 5 parts of bismaleimide resin and 0.5 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is carried out for 15 minutes to obtain a first mixed product;
[0115] Second mixing stage: add 0.1 parts of curing agent 1 and 0.1 parts of curing agent 2 to the first mixed product and mix them, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;
[0116] The third mixing stage: add 34 parts of conductive filler 1 and 1 part of conductive filler 2 to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes to obtain a thermosetting conductive adhesive; then add 2 parts of diluent to the thermosetting conductive adhesive, control the stirring speed to 30 rpm, stir for 10 minutes, and continue stirring for 20 minutes in a vacuum environment, then discharge the material to obtain a thermosetting conductive adhesive A4.
[0117] Example 5
[0118] First mixing stage: 2 parts of functional epoxy resin 2, 2.5 parts of acrylate resin 1, 5 parts of bismaleimide resin and 0.5 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is carried out for 15 minutes to obtain a first mixed product;
[0119] Second mixing stage: add 0.1 parts of curing agent 1 and 0.1 parts of curing agent 2 to the first mixed product and mix them, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;
[0120] The third mixing stage: add 34 parts of conductive filler 1 and 1 part of conductive filler 2 to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes, and obtain thermosetting conductive adhesive A5.
[0121] Example 6
[0122] First mixing stage: 3 parts of 2 functional epoxy resins, 2 parts of 2 acrylic resins, and 4 parts of epoxy-modified PP prepolymers are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;
[0123] Second mixing stage: add 0.6 parts of curing agent 1 and 0.2 parts of curing agent 2 to the first mixed product and mix them, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;
[0124] The third mixing stage: add 34 parts of conductive filler 1 and 1 part of conductive filler 2 to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes to obtain a thermosetting conductive adhesive; then add 1 part of diluent to the thermosetting conductive adhesive, control the stirring speed to 30 rpm, stir for 10 minutes, and continue stirring for 20 minutes in a vacuum environment, then discharge the material to obtain a thermosetting conductive adhesive A6.
[0125] Example 7
[0126] First mixing stage: 3 parts of 2 functional epoxy resins, 2 parts of 1 acrylic resin, and 4 parts of epoxy-modified PP prepolymers are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;
[0127] Second mixing stage: add 0.6 parts of curing agent 1 and 0.2 parts of curing agent 2 to the first mixed product and mix them, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;
[0128] The third mixing stage: add 34 parts of conductive filler 1 and 1 part of conductive filler 2 to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes to obtain a thermosetting conductive adhesive; then add 1 part of diluent to the thermosetting conductive adhesive, control the stirring speed to 30 rpm, stir for 10 minutes, and continue stirring for 20 minutes in a vacuum environment, then discharge the material to obtain a thermosetting conductive adhesive A7.
[0129] Comparative Example 1
[0130] First mixing stage: 7 parts of functional epoxy resin and 1 part of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;
[0131] Second mixing stage: add 2 parts of curing agent 1 and 0.1 parts of curing agent 2 to the first mixed product and mix them, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;
[0132] The third mixing stage: add 40 parts of conductive filler 1 and 1 part of conductive filler 2 to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes to obtain a thermosetting conductive adhesive; then add 1 part of diluent to the thermosetting conductive adhesive, control the stirring speed to 30 rpm, stir for 10 minutes, and continue stirring for 20 minutes in a vacuum environment, then discharge the material to obtain a comparative adhesive B1.
[0133] Comparative Example 2
[0134] The first mixing stage: 8 parts of acrylic resin 1 and 1 part of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;
[0135] Second mixing stage: add 1.5 parts of curing agent 1 and 0.1 parts of curing agent 2 to the first mixed product and mix them, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;
[0136] The third mixing stage: add 40 parts of conductive filler 1 and 1 part of conductive filler 2 to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes to obtain a thermosetting conductive adhesive; then add 1 part of diluent to the thermosetting conductive adhesive, control the stirring speed to 30 rpm, stir for 10 minutes, and continue stirring for 20 minutes in a vacuum environment, then discharge the material to obtain a comparative adhesive B2.
[0137] Comparative Example 3
[0138] The preparation process of Comparative Example 3 is the same as that of Example 3, except that the parts of the raw materials are different, specifically, 6 parts of the functional epoxy resin 1 and 6 parts of the functional epoxy resin 2, and finally a comparative example adhesive B3 is obtained.
[0139] Comparative Example 4
[0140] Hot melt glue B4 is used, which comes from DZ230326B of Tuodi Chemical.
[0141] It should be noted that in the above embodiments and comparative examples, the functional epoxy resin 1 is commercially available Sumitomo Chemical ELM-100H (containing epoxy groups), the functional epoxy resin 2 is commercially available Shin-Nakamura Chemical EA-1010N (containing epoxy groups and active groups), the acrylate resin 1 is commercially available Sadomar CN 966H90, the acrylate resin 2 is commercially available Sadomar CN 9014NS, the bismaleimide resin is commercially available HR-YSP of Printec, the toughening agent is commercially available Daicel PB-3600, the diluent is commercially available Mitsubishi Chemical GMA, the curing agent 1 as a latent curing agent is derived from the commercially available Asahi Kasei HX-3722, the curing agent 2 as a peroxide curing agent is derived from the commercially available Nouryon TRIGONOX 21S, the conductive filler 1 is commercially available VALE Ni-100, and the conductive filler 2 is commercially available Cabot VXC-72.
[0142] In addition, in the above embodiments and comparative examples, the preparation process of epoxy-modified PP prepolymer is as follows: 9 parts of maleic anhydride grafted polypropylene are weighed and added to the reaction container, and the temperature is raised to 150°C for melting; 1 part of polypropylene glycol diglycidyl ether is weighed and added to the reaction container, vacuumed, and the stirring speed is controlled at 200-500rpm to make the reaction system uniformly mixed; after uniform mixing, 0.5 parts of triphenylphosphine are added to the reaction container, the temperature is raised to 170°C, and the temperature in the reaction container is ensured to be 160°C ± 5°C, and the reaction is carried out for 2h, and the reaction process is carried out in a vacuum environment throughout; after the reaction is complete, the material is discharged and cooled to obtain epoxy-modified PP prepolymer. Among them, the maleic anhydride grafted polypropylene is Dow's GA1000R.
[0143] The raw material component information of the thermosetting conductive adhesives A1 to A7 obtained in the above embodiments as adhesives and the adhesives B1 to B3 obtained in the comparative examples are calculated in parts by weight, as shown in the following Table 1:
[0144] Table 1. Statistical table of raw material components of adhesives in Examples and Comparative Examples
[0145]
[0146]
[0147] In order to verify the performance of adhesives A1 to B3 and hot melt adhesive B4 prepared in each embodiment and comparative example, the following performance tests were performed on A1 to B4 respectively:
[0148] (1) Curing time test:
[0149] Adhesives A1 to B3 were dropped between two metal sheets (copper foil) respectively, and then hot pressed at 180°C, with the hot pressing time increasing by 1s in steps starting from 1s. After hot pressing, the two metal sheets were taken out and torn apart. If the glue inside was not cured by visual judgment, a new sample was prepared for subsequent time period testing. If the glue inside was cured by visual judgment, a part of the cured product was taken for DSC testing to observe whether an exothermic peak would appear. If an exothermic peak appeared, a new sample was prepared for subsequent time period testing. If no exothermic peak appeared, the corresponding hot pressing time was the 180°C hot pressing curing time. The curing time of hot melt adhesive B4 was recorded as NA.
[0150] (2) Peel strength test:
[0151] 1) Sample preparation: Copper foil was used as the substrate, and the adhesives A1 to B3 and the hot melt adhesive B4 prepared in each embodiment and comparative example were respectively scraped on different substrates by a scraper, and cured to form a film with a thickness of 20 μm (i.e., a cured product film), which was then cut into a size of 20 mm×100 mm to obtain a sample;
[0152] 2) Peel strength test before soaking: fix the substrate of the sample on the back plate, peel the film of the sample at 90°, test the 90° peel force, and the peeling speed is 50 mm / min. After testing 3 samples in each embodiment and comparative example, take the average value to obtain the peel strength before soaking.
[0153] 3) Peel strength test after soaking:
[0154] The sample was placed in an electrolyte, sealed, and placed in an oven at 85°C for 24 hours, then taken out and tested for 90° peeling strength; the peeling speed was 50 mm / min, and 3 samples were tested for each embodiment and comparative example, and the average value was taken to obtain the peeling strength after soaking.
[0155] (3) Dissolution rate and swelling rate test:
[0156] 1) Dissolution rate test: Take 1.4±0.1g of adhesives A1~B3 and hot-melt glue B4 prepared in each embodiment and comparative example, record the mass as M1, soak them in 7±0.5g electrolyte, record the mass as M2, then seal them with a syringe bottle, put them in an oven at 85℃, and after aging for 24 hours, take 20±5mg of the clear liquid, heat it to 300℃ at a rate of 10℃ / min using a thermogravimetric analyzer (TGA), read the weight percentage of the residual material, record it as A, and calculate the dissolution rate according to the formula A×M2 / M1.
[0157] 2) Swelling rate test: Take 2±0.1g of the adhesives A1~B3 prepared in each embodiment and comparative example and the hot melt glue B4, record the mass as M1, soak them in 50g of electrolyte, put them in an 85℃ oven, age for 24 hours, take out the glue block, wipe off the electrolyte on its surface, weigh it to get M2, and calculate the swelling rate according to the formula (M2-M1)×100% / M1.
[0158] (4) Contact resistance test:
[0159] Use the same amount of A1 to B4 to bond the tabs and copper foil to make samples, and perform hot pressing (the hot pressing time is longer than the curing time, and the B4 sample does not need hot pressing). After hot pressing, take out the sample and connect the two probes of the resistor to the copper foil and the tab respectively. Read the value of the resistor, which is the contact resistance of the glue. Soak the hot-pressed sample in electrolyte, place it in an 85℃ oven, age it for 24 hours, take it out and wipe off the electrolyte on its surface, and then test it in the same way to obtain the contact resistance of the glue at 85℃ / 24h. If the tabs and copper foil fall off after soaking, the contact resistance after soaking is recorded as NG.
[0160] The test results of adhesives A1 to B3 and hot melt adhesive B4 in various embodiments and comparative examples are summarized in Table 2 below.
[0161] Table 2. Performance test data statistics
[0162]
[0163] The advantages of the embodiments of the present application are analyzed in combination with Table 1 and Table 2.
[0164] The thermosetting conductive adhesives A1-A7 obtained in each embodiment 1-7 are mainly made of functional epoxy resin, acrylate resin, curing agent and conductive filler as raw materials; wherein, the functional epoxy resins all contain epoxy groups, and compared with comparative examples 1-3, preliminary curing or complete curing can be achieved within 1-6 seconds at 180°C, and the peel strength before and after soaking can be maintained at a high level. The thermosetting conductive adhesives A1-A7 obtained in each embodiment have high bonding strength and stability, and the dissolution rate of the cured product at 85°C / 24h in an electrolyte environment is not higher than 0.7%, and the swelling rate at 85°C / 24h is not higher than 4.5%. The cured product can still maintain high bonding stability under long-term resistance to electrolyte erosion, and can maintain low contact resistance at room temperature and 85°C / 24h, and has excellent conductive performance.
[0165] Specifically, compared with the embodiments, comparative example 1, comparative example adhesive B1 does not contain acrylate resin, resulting in a too long curing time, low peel strength, and weak bonding force.
[0166] Comparative Example 2 Compared with the embodiments, the comparative example adhesive B2 does not contain the functional epoxy resin, resulting in weaker electrolyte resistance and larger swelling rate and dissolution rate.
[0167] Comparative Example 3 Compared with the embodiments, the comparative example adhesive B3 contains more than 10 parts of functional epoxy resin, which leads to a long curing time, low peel strength and weak bonding force.
[0168] Comparative Example 4 uses hot melt glue B4. Compared with the embodiments, the dissolution rate and swelling rate at 85°C / 24h are too high, and high-temperature rapid curing cannot be achieved, which is not conducive to the application in the bonding of lithium battery pole pieces and pole ears.
[0169] It is worth noting that, compared with Example 4, and compared with Example 5, Example 3, the raw material of the thermosetting conductive adhesive has a shorter curing time under 180°C hot pressing conditions by introducing bismaleimide resin, and the peel strength before soaking and the peel strength after soaking at 85°C / 24H are higher, and the swelling rate at 85°C / 24H is lower, and the thermosetting conductive adhesive has higher bonding strength and stability.
[0170] Compared with Example 2, Example 6 and Example 7 respectively have higher peel strength before soaking and peel strength after soaking at 85°C / 24H by introducing epoxy-modified PP prepolymer into the raw materials of the thermosetting conductive adhesive of Example 6 and Example 7, and lower swelling rate at 85°C / 24H, so the thermosetting conductive adhesive has higher bonding strength and stability.
[0171] At this point, the embodiment of the present application has excellent bonding properties, conductivity and electrolyte resistance after thermal curing through the component design of the thermosetting conductive adhesive. When used in the lithium battery production process, the pole pieces and the pole ears can be directly bonded with the thermosetting conductive adhesive to replace the traditional technology of welding to connect the pole pieces and the pole ears, thereby avoiding the formation of burrs, welding slag, welding spots and metal particles during welding, and there is no need to use protective tape to cover the pole pieces, thereby effectively improving the safety and energy density of the battery.
[0172] The various technical features described above can be combined arbitrarily. Although all possible combinations of these technical features are not described, any combination of these technical features should be considered to be covered by this specification as long as there is no contradiction in such combination.
[0173] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A thermosetting conductive adhesive, characterized in that: The raw materials of the thermosetting conductive adhesive include functional epoxy resin, acrylate resin, curing agent and conductive filler; The functional epoxy resin contains epoxy groups, and the functional epoxy resin and the acrylate resin are used to undergo a cross-linking reaction under the action of a curing agent.
2. The thermosetting conductive adhesive according to claim 1, characterized in that: In parts by weight, the raw materials of the thermosetting conductive adhesive include: Functional epoxy resin: 1-10 parts; acrylate resin: 1-5 parts; curing agent: 0.1-5 parts; conductive filler: 20-45 parts.
3. The thermosetting conductive adhesive according to claim 1, characterized in that: The functional epoxy resin further contains at least one active group, and the active group is used for coordinated cross-linking reaction with the acrylate resin under the action of a curing agent; Optionally, the active group includes at least one of a double bond or a hydroxyl group; Optionally, the functional epoxy resin includes one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, aminophenol epoxy resin, and naphthol epoxy resin; Optionally, the acrylate resin includes at least one of aliphatic polyurethane acrylate or polybutadiene-modified polyurethane acrylate; Optionally, the curing agent includes a latent curing agent and a peroxide curing agent, and the mass ratio of the latent curing agent to the peroxide curing agent is (1-20):
1.
4. The thermosetting conductive adhesive according to claim 3, characterized in that: The raw materials of the thermosetting conductive adhesive further include at least one of bismaleimide resin, toughening agent or diluent; Optionally, in the raw materials of the thermosetting conductive adhesive, in parts by weight: the bismaleimide resin is 0.01-10 parts; and / or the toughening agent is 0.01-5 parts; and / or the diluent is 0.01-5 parts.
5. The thermosetting conductive adhesive according to claim 4, characterized in that: Meet at least one of the following conditions: A, the peroxide curing agent comprises at least one of tert-butyl peroxy-2-ethylhexanoate, tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxybenzoate or dibenzoyl peroxide; B. The latent curing agent includes at least one of an amine curing agent, a phosphorus curing agent or an imidazole curing agent; C. The conductive filler includes at least one of superconducting carbon, graphite, hard carbon, silver powder, silver-coated copper powder, silver-coated nickel powder, nickel powder, silver-coated glass, silver-coated graphite, tin-silver-copper powder or carbon nanotubes; Optionally, the particle size of the conductive filler is in the range of 0.2-100 μm; D. The bismaleimide resin includes at least one of N,N'-1,3-phenylene bismaleimide, 1,2-phenylene-bis-maleimide or N,N'-1,4-phenylene dimaleimide; E. The toughening agent includes at least one of polybutadiene rubber or nitrile rubber; F. The diluent includes at least one of a glycidyl ether diluent, a glycidyl ester diluent or a cyclobutane oxide diluent.
6. The thermosetting conductive adhesive according to claim 4, characterized in that: At least one of the following conditions is met: G. The functional epoxy resin includes at least one of epoxy resin jER 604, jER 630, ELM-100H, 4032D, N730A, 7200H, 4088 or EA-1010N; H. The acrylate resin includes at least one of acrylate resins CN 966H90, CN 9014NS, BR-641S or BR-643; I. The latent curing agent includes at least one of curing agents AJICURE PN-40, AJICURE PN-50, AJICURE MY-24, AJICURE MY-25, FXR-1030, FXR-1081, FXE-1000, NOVACURE 3922HP, NOVACURE HX-A3932HP, NOVACURE HX-3941, NOVACURE HX-3042, NOVACURE HX-3742, NOVACURE HX-3088, and HX-3792; J. The toughening agent specifically includes at least one of epoxidized polybutadiene, polybutadiene-modified acrylate or core-shell rubber epoxy dispersion; K. The diluent includes at least one of diluent OXT-212, OXT-221, OXT-213, OXT-101, ED509S, E10P, EX201 or GMA; L. In parts by weight, the raw materials of the thermosetting conductive adhesive further include: epoxy-modified PP prepolymer: 1-10 parts; optionally, the molecular weight of the epoxy-modified PP prepolymer is 1000-100000.
7. A method for preparing a thermosetting conductive adhesive according to any one of claims 1 to 6, characterized in that: The process comprises uniformly mixing functional epoxy resin, acrylate resin, curing agent and conductive filler in a predetermined proportion to obtain a thermosetting conductive adhesive.
8. The method for preparing the thermosetting conductive adhesive according to claim 7, characterized in that: The specific steps include: The first mixing stage: at least one of the optional bismaleimide resin, toughening agent or epoxy-modified PP prepolymer is mixed evenly with the functional epoxy resin and the acrylate resin to obtain a first mixed product; The second mixing stage: adding the curing agent to the first mixed product and mixing evenly to obtain a second mixed product; The third mixing stage: uniformly dispersing the conductive filler in the second mixed product to obtain a thermosetting conductive adhesive.
9. The method for preparing the thermosetting conductive adhesive according to claim 8, characterized in that: The third mixing stage also includes adding a predetermined proportion of diluent into the thermosetting conductive adhesive and mixing; Optionally, dispersing the conductive filler in the second mixed product includes a first dispersing stage and a second dispersing stage performed sequentially; Optionally, the first mixing stage, the second mixing stage and the third mixing stage are all carried out under stirring conditions; Optionally, in the first mixing stage or the second mixing stage: the stirring speed of the mixing container is controlled within the range of 5-60 rpm, and the stirring time is controlled within the range of 10-30 min; Optionally, the stirring speed of the mixing container in the first dispersing stage is controlled within the range of 5-60 rpm, and the stirring time is controlled within the range of 10-30 min; Optionally, the stirring speed of the mixing container in the second dispersion stage is controlled within the range of 30-100 rpm, the dispersion speed of the mixing container is controlled within the range of 600-1000 rpm, the stirring time is controlled within the range of 10-30 min, and the mixing temperature is controlled below 30° C.; Optionally, the adding of a predetermined proportion of diluent to the thermosetting conductive adhesive includes a mixing stage and a vacuum degassing stage performed sequentially, and the stirring speed of the mixing container during the mixing stage and the vacuum degassing stage is controlled within the range of 5-60rpm, and the stirring time is controlled within the range of 10-30min.
10. The thermosetting conductive adhesive according to any one of claims 1 to 6, wherein the thermosetting conductive adhesive is used for bonding lithium battery pole pieces and tabs.
Citation Information
Cited By
Conductive non-woven fabric adhesive tape and preparation method thereof
CN120775508A